Report of a case of Marjolin’s Ulcer in a patient with multiple burn scars during Plastic Surgical Treatment: surgical resolution aimed at maintaining functional knee. - Bocchi, Francesca; Zermani, Rita (Acta Biomedica Atenei Parmensis, 2013)
Marjolin’s ulcer is an epithelial neoplasm of the skin that can appear in a multitude of slow-tosolve cutaneous lesions. It is a relatively rare condition, with an estimated 3-5% occurrence among all squamocellular carcinomas of the skin (1). We present the clinical case of a female patient with previous third-degree burn scars who had already undergone numerous surgical procedures and presented recurring ulcers, above all on the extensor surface of the lower limbs. She was placed under our care so that she could undergo procedures for the debridement of these lesions, histological examinations and skin autografting. The clinic case described here is designed to underline the importance of the early monitoring and treatment of skin lesions that are difficult to heal in order to prevent malignant neoplastic degeneration, or at least halt its progress.